Tema procrastination pada film animasi 2D “Udah Besok Aja” - Mahasena, Ghoris Arkan; Miyosa, Atmaja Septa (Visualita Jurnal Online Desain Komunikasi Visual, 2022)
One of the social criticisms of the young workforce is regarding the attitude of procrastination. This counterproductive attitude needs to be addressed and requires educational media. The main problem is the need for the right media that can convey the message and entertain the target audience. The aim is to create short 2-dimensional animated films with effective techniques. The result is an animated film product entitled Udah Besok Aja, which is produced using the frame by frame technique. The method use 2d animation process. The film Udah Besok Aja presents a story that shows the cause and effect associated with procrastination. Pre-production includes extracting story ideas, synopsis, character design, visual background, to storyboards. Film production includes the process of making images with rough-pass, clean-line, in between and lipsync. The application uses Adobe Animate. Post-production is done by compositing, rendering and publishing. In conclusion, the creation of a short 2-dimensional animated film with the title Udah Besok Aja succeeded in presenting the main message, namely criticism of the attitude of procrastinating work. The message is conveyed through the storyline, the choice of words in the dialogue, and the expression of the main character.